THE PROFILE OF 8TH JUNIOR HIGH SCHOOL STUDENTS' QUESTION SKILL BASED ON QUESTION CATEGORY SYSTEM FOR SCIENCE (QCSS) ON HUMAN RESPIRATORY - Syahida Ainaya, - (2021)
Questions in science learning are an undeniable need. Improving understanding and thought processes will be greatly helped by the habit of asking questions. Regarding questions skills in science education. There are various types of questions, but the extent to which students' questioning skills are currently rarely analyzed. Therefore, this study aims to analyze the student's question skills. identifying three levels of questions using the Question Category System for Science. The Question category for science (QCSS) is used as a rubric for analyzing questions, with scientific articles on the topic of the human respiratory system. A total of 100 students with a total of 572 questions were analyzed. The results showed that as many 77% of closed questions in the first article and 79% of closed questions in the second article were asked by students, with an analysis at the second level of 77% in the first and second articles. as many 74% of the questions included in the type of cognitive memory operation. While the third level questions are dominated by the type of CMO1 questions, namely (remembering including repeating and imitating, memorizing definitions) as much 64% in the first article and as much 55% in the second article. These results show the analysis of questions using QCSS can show that students are dominated by low-level questioning training which aims to develop search skills because one of the closed-type questions is looking for differences or similarities. Although there have two articles that have the possibility to ask high-level questions.